1994
DOI: 10.1038/372455a0
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic oxidation of hydrocarbons in crude oil by new types of sulphate-reducing bacteria

Abstract: Many crude oil constituents are biodegradable in the presence of oxygen; however, a substantial anaerobic degradation has never been demonstrated. An unusually low content of n-alkanes in oils of certain deposits is commonly attributed to selective utilization of these hydrocarbons by aerobic microorganisms. On the other hand, oil wells and production fluids were shown to harbour anaerobic sulphate-reducing bacteria, but their actual electron donors and carbon sources were unknown. On the basis of nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
259
3
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 446 publications
(277 citation statements)
references
References 20 publications
6
259
3
4
Order By: Relevance
“…The high microbial sulfide production in these sediments fosters patchy mats of sulfide-oxidizing bacteria such as Beggiatoa (Jannasch et al, 1989). From such areas, a variety of sulfate-reducing bacteria (Rueter et al, 1994;Jeanthon et al, 2002), sulfate-reducing archaea (Burggraf et al, 1990;Khelifi et al, 2010) and methanogenic archaea (Kurr et al, 1991) have been isolated.…”
Section: Introductionmentioning
confidence: 99%
“…The high microbial sulfide production in these sediments fosters patchy mats of sulfide-oxidizing bacteria such as Beggiatoa (Jannasch et al, 1989). From such areas, a variety of sulfate-reducing bacteria (Rueter et al, 1994;Jeanthon et al, 2002), sulfate-reducing archaea (Burggraf et al, 1990;Khelifi et al, 2010) and methanogenic archaea (Kurr et al, 1991) have been isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial studies of subsurface ecosystems, such as oilfields, have shown the presence of fermentative bacteria (Bernard et al, 1992;Bhupathiraju et al, 1991 ;Bhupathiraju & McInerney, 1993;DavydovaCharakhch'yan et al, 1993b;Fardeau et al, 1996;Holloway et al, 1980;Jeanthon et al, 1995;L'Haridon et al, 1995;Ravot et al, 1995;Stetter et al, 1993), sulfate reducers (Bhupathiraju & McInerney, 1993 ;Cord-Ruwisch et al, 1987 ;Nazina & Rozanova, 1978;Nilsen et al, 1996;Rees et al, 1995;Rozanova & Nazina, 1979;Rozanova & Galushko, 1990;Rozanova et al, 1989;Rueter et al, 1994;Stetter et al, 1993;Tardy-Jacquenod et al, 1996;Voordouw et al, 1996), and acetogens (Davydova-Charakhch'yan et al, 1993b). It has been established that methanogens…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of oxygen, mono-and dioxygenases catalyze the oxidative functionalization of recalcitrant compounds, i.e., hydrocarbons. Microbial mineralization of such substances also occurs in nature in the absence of molecular oxygen, and in the last decade anaerobic bacteria have been isolated on substances such as alkylbenzenes (6,18,22), alkanes (1,7,25,26), and alkenes (15). Thus far, the biochemistry of the initial activation reactions has been revealed only for toluene.…”
mentioning
confidence: 99%